Lotus Esprit : the complete story. / Jeremy Walton. - Walton, Jeremy, 1946- (Crowood, 1997)
Written by an experienced motoring author, this book offers a comprehensive history of the Lotus Esprit, complete with full technical specifications, details of all versions of the Esprit, and advice on buying and running an Esprit in the 1990s.